Assessing the COVID-19 Vaccine Hesitancy: Validation of the Moroccan Version of the C19-VHS Questionnaire and Analysis of Sociodemographic Factors - FELLAQ , Sara EL; DAHOU, Badreddine; SENNANI, Sara; LAHROUZ, Mustapha; Bouziani, Amina; Mohammed, Chahboune (Bangladesh Journal of Medical Science, 2025)
Background Vaccine hesitancy has been a major obstacle in the fight against COVID-19. Objective: This study aims to explore the factors influencing COVID-19 vaccine hesitancy among a sample of 800 Moroccan participants aged 18 and older. Methodology The COVID-19 Vaccine Hesitancy Scale (C19-VHS), translated and validated in Arabic, was used to measure various aspects of this hesitancy. The translation methodology included a two-step translation process, followed by back-translation and cultural validation. A confirmatory factor analysis (CFA) revealed a unidimensional structure explaining 63.98% of the variance, with a Cronbach’s alpha of 0.903, indicating excellent internal consistency. Results The results show that vaccine hesitancy is influenced by several sociodemographic factors. A negative correlation with age suggests that older individuals are less hesitant. In contrast, education level and health status are positively correlated with hesitancy. A majority of participants expressed moderate to strong vaccine hesitancy, while only 2% fully accepted vaccines. Conclusion These findings highlight the need for targeted awareness strategies to improve perceptions of vaccine efficacy and safety. Specific interventions are essential to strengthen trust in vaccines and increase vaccine uptake among the Moroccan population. BJMS, Vol. 24 No. 03 July’25 Page : 873-880